2010
DOI: 10.1245/s10434-010-1151-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of E-cadherin Expression and Peripheral Blood Micrometastasis in Gastric Carcinoma Patients

Abstract: In conclusion, loss of normal E-cad expression in gastric cancer showed a close correlation with the presence of PBMM. PBMM was associated with poor RFS independent of other clinicopathological features. Additionally, detection of PBMM was a significant indicator of OS, and intensive chemotherapy seems to be indicated for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The major cause of death from GC is the inability to detect and prevent metastasis at an early stage of disease. Several studies investigating the presence of CTCs in gastric cancer patients have been reported in the literature, but both the CTC detection techniques used and the results obtained were heterogeneous [15–17]. And most of these studies focused on the sensitivity and specificity of CTCs isolation, as well as the relationship between CTCs and cancer relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of death from GC is the inability to detect and prevent metastasis at an early stage of disease. Several studies investigating the presence of CTCs in gastric cancer patients have been reported in the literature, but both the CTC detection techniques used and the results obtained were heterogeneous [15–17]. And most of these studies focused on the sensitivity and specificity of CTCs isolation, as well as the relationship between CTCs and cancer relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Snail bind to E-boxes in the E-cadtherin promoter to repress gene transcription and induce cell migration and invasion[32]. In many human cancers, there is an inverse relationship between E-cadherin and Snail expression[9, 13, 18, 36-39]. Although Snail was associated with invasion and lymph node metastasis in many human cancers; the role of Snail in SOD2-induced TSCC invasion had not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CTCs in circulation suggests not only a high risk of tumor recurrence, but also an unfavorable clinical outcome even in the early stages of GC [20]. The prognostic impact of CTCs in GC has been reported in several studies [21][22][23][24][25][26][27]. The sensitivity of RT-PCR CTC detection was superior to the other less commonly used cytological detection methods involving fluorescence-activated cell sorting (FACS), immunohistochemistry (IHC), and immunocytochemistry (ICC) [20].…”
Section: Gastric Cancer (Gc)mentioning
confidence: 98%